Influence of Club Facilities and Equipment on Talent Identification for Players in Rugby Clubs in Kenya - Otieno, Michael D.; Nteere, Jacob; Onywera, Vincent; Akala, Winston (American Journal of Creative Education, 2020)
The purpose of this study was to investigate the influence of club facilities and equipment on talent identification for players in rugby clubs in Kenya. The club facilities and equipment included rugby pitch, gymnasium, scrum machine, tackle bags, tackle suits, hit shields, balls and marker cones. Data were collected using Questionnaires and interviews from rugby players (n= 125) and coaches (n=15) during the 2017/2018 Kenya Rugby Union league competition. Data were analyzed through both descriptive and inferential statistics of Chi- square test of independent measures. A null hypothesis stating that there is no significant difference in the mean rugby talent identification index when the influence of the rugby players’ club facilities and equipment is classified as high or low was tested. Despite the coaches view that availability of facilities and equipment has an influence on the talent identification process, the findings indicate that there is no evidence that rugby club facilities and equipment plays a significant role in talent identification for rugby players in rugby clubs in Kenya. The study however recommends that the rugby clubs should invest in good facilities and equipment as this would go a long way in ensuring player safety and minimizing the risk of injury during the talent identification process. Other studies involving the rest of the socio-cultural attributes that are likely to impact on talent identification like family, coaches, schools, peers, need to be conducted.